2017
DOI: 10.3390/geosciences7030073
|View full text |Cite
|
Sign up to set email alerts
|

Glaciers, Permafrost and Lake Levels at the Tsengel Khairkhan Massif, Mongolian Altai, During the Late Pleistocene and Holocene

Abstract: Understanding paleo—and recent environmental changes and the dynamics of individual drivers of water availability is essential for water resources management in the Mongolian Altai. Here, we follow a holistic approach to uncover changes in glaciers, permafrost, lake levels and climate at the Tsengel Khairkhan massif. Our general approach to describe glacier and lake level changes is to combine traditional geomorphological field mapping with bathymetric measurements, satellite imagery interpretation, and GIS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…(Figure 1a, b). Glacial advances from the south‐western slopes of the Tsengel Khairkhan Mountains left prominent moraine lobes during the last glaciation which blocked the valley and formed the endorheic Khar Nuur basin (Figure 1b) (Walther et al, 2017). The bedrock of most parts of the catchment is composed of friable black clay shales, whereas only the morainal deposits in the western parts of the catchment consist of granite.…”
Section: Study Sitementioning
confidence: 99%
“…(Figure 1a, b). Glacial advances from the south‐western slopes of the Tsengel Khairkhan Mountains left prominent moraine lobes during the last glaciation which blocked the valley and formed the endorheic Khar Nuur basin (Figure 1b) (Walther et al, 2017). The bedrock of most parts of the catchment is composed of friable black clay shales, whereas only the morainal deposits in the western parts of the catchment consist of granite.…”
Section: Study Sitementioning
confidence: 99%
“…The spatial patterning of the present coverage suggests that south-facing margins were most significantly impacted by the ice loss, especially at lower elevations.
Figure 2 Ice extent in Tsengel region from 1990 through 2016, using glacier outlines Khairkhan from the Global Land Ice Measurements from Space (GLIMS) database 51 , 52 , modified from Walther et al 53 Ice Patch Survey boxes represent areas identified with more permanent ice (2010–2020) where we conducted intensive surveys of the maximum melt extent in August 2019. Inset shows the location of the study area relative to the boundary of the Pleistocene glaciation.
…”
Section: Resultsmentioning
confidence: 99%
“…Ice extent in Tsengel region from 1990 through 2016, using glacier outlines Khairkhan from the Global Land Ice Measurements from Space (GLIMS) database 51,52 , modified from Walther et al 53 Pedestrian and horseback survey. Our survey of five ice patches and one glacier margin revealed three localities bearing artifacts and ancient biological material, as well as one locality where faunal remains, with no direct evidence of a cultural origin, were recovered from periglacial pools frozen at the time of recovery (Supplementary Fig.…”
Section: Figurementioning
confidence: 99%
“…Potential exists in using more comprehensive metrics including the normalized difference in air and ground temperatures [60] and changes in volumetric water content [61]. The possibility for the derivation of these metrics is increasing as Mongolia continues to develop their borehole and climate monitoring networks [62,63].…”
Section: Assumptions and Limitationsmentioning
confidence: 99%